2006
DOI: 10.1089/jwh.2006.15.941
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Survival by Socioeconomic Status, Race/Ethnicity, and Place of Residence in Texas, 1995–2001

Abstract: SES and race/ethnicity were independently associated with poorer cervical cancer survival in this large Texas sample. Further research is needed to investigate the role of optimal treatment and comorbid conditions in the association between SES and cervical cancer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 33 publications
(43 reference statements)
4
61
1
Order By: Relevance
“…Several previous studies have evaluated race specifically as a predictor of survival for women with cervical cancer. 4,5,7,8,[32][33][34][35][36][37][38] Four of 10 studies demonstrated that AA women had worse survival compared with white women despite adjustment for several potential confounder variables, 5,8,32,36 whereas 6 of 10 studies showed no racial differences in survival after multivariate adjustment. 4,[33][34][35]37,38 Thoms et al 34 reported no survival differences between AA women and white women after adjustment for stage, age and histology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have evaluated race specifically as a predictor of survival for women with cervical cancer. 4,5,7,8,[32][33][34][35][36][37][38] Four of 10 studies demonstrated that AA women had worse survival compared with white women despite adjustment for several potential confounder variables, 5,8,32,36 whereas 6 of 10 studies showed no racial differences in survival after multivariate adjustment. 4,[33][34][35]37,38 Thoms et al 34 reported no survival differences between AA women and white women after adjustment for stage, age and histology.…”
Section: Discussionmentioning
confidence: 99%
“…In articles that examined cervical cancer survival and SES, 6,7,14,16-23 6 of 11 studies indicated that women with lower SES had poorer survival. 6,7,17,[20][21][22] Eggleston et al 7 reported on 5467 women with cervical cancer. In their study, an SES variable was defined by using measures of employment, income, education, and poverty at the zip code level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Common factors of SES include income, [3][4][5][6][7] education, [3][4][5][6][7] occupation, 7,8 place of residence, 9 poverty level, 5,7,8 and race. [2][3][4][5] For the purpose of defining SES more comprehensively, these measures are frequently combined, because each indicator alone is considered inadequate to reflect SES.…”
mentioning
confidence: 99%
“…14 The body of research that links SES to potentially human papillomavirus (HPV)-associated cancers is sparse and has primarily focused on the HPV to cervical cancer relation. 9,[15][16][17][18][19][20][21][22][23][24][25] In a sample of women living in Brazil, poverty and access to care inequities were found to be predictive of oncogenic-type HPV and, ultimately, of cervical cancer. 21 A meta-analysis based upon 57 studies found that there was a 2-fold increased risk of invasive cervical cancer among individuals of low social status compared with individuals of high social status.…”
mentioning
confidence: 99%